Computer-aided design of two-photon-absorbing organic chromophores - Petrusevich, Lizaveta (Politechnika Wrocławska, 2023)
The doctoral dissertation is devoted to the computer-aided design of fluorescent probes with two-photon absorption properties tailored for bioimaging applications. The dissertation encompasses two objectives: i) the design of novel probes with significant two-photon absorption strengths, and ii) the development of entirely non-empirical computational protocol for robust and cost-effective simulations of vibrationally-resolved absorption spectra. Organic dyes containing tetra-coordinated boron atom were studied in this thesis on account of their good photophysical properties.
Keywords: computational chemistry; computational spectroscopy; two-photon absorption; organoboron complexes; fluorescent probes